Neutron activation autoradiography and scanning macro-XRF of Rembrandt van Rijn’s Susanna and the Elders (Gemäldegalerie Berlin): a comparison of two methods for imaging of historical paintings with elemental contrast - Alfeld, Matthias; Laurenze-Landsberg, Claudia; Denker, Andrea; Janssens, Koen; Noble, Petria (Applied physics. A, Materials science & processing, 2015)
Imaging methods with elemental contrast are of great value for the investigation of historical paintings, as they allow for study of sub-surface layers that provide insight into a painting’s creation process. Two of the most important methods are neutron activation autoradiography (NAAR) and scanning macro-XRF (MA-XRF). Given the differences between these methods in the fundamental physical phenomena exploited, a theoretical comparison of their capabilities is difficult and until now a critical comparison of their use on the same painting is missing. In this paper, we present a study of Rembrandt van Rijn’s painting Susanna and the Elders from the Gemäldegalerie in Berlin employing both techniques. The painting features a considerable number of overpainted features and a wide range of pigments with different elemental tracers, including earth pigments (Mn/Fe), Azurite (Cu), lead white (Pb), vermilion (Hg) and smalt (Co, As). MA-XRF can detect all elements above Si ( Z = 14), suffers from few spectral overlaps and can be performed in a few tens of hours in situ, i.e. in a museum. NAAR requires the stay of the painting at a research facility for several weeks, and inter-element interferences can be difficult to resolve. Also, only a limited number of elements contribute to the acquired autoradiographs, most notably Mn, Cu, As, Co, Hg and P. However, NAAR provides a higher lateral resolution and is less hindered by absorption in covering layers, which makes it the only method capable of visualizing P in lower paint layers.